TAHAPAN PERKEMBANGAN SMART CITY KOTA DENPASAR TAHUN 2016-2023 - Amin Bahtiar; Achmad Djunaedi (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
Denpasar City began implementing smart city in 2016 by integrating the concept with Balinese local wisdom values, especially Tri Hita Karana, which focuses on harmony between God, humans, and nature. The application of local wisdom in smart city development in Denpasar City has received various appreciations, even winning the Indonesian Smart City Index award in 2019. The purpose of this study is to describe the stages of smart city development in Denpasar City and identify the factors that influence the stages of smart city development in Denpasar City. This study uses an abductive-qualitative approach with a case study methodology. The study results show that the stages of smart city development in Denpasar City consist of five stages: preparation, planning, implementation, emergency response to Covid-19, and implementation (continuation) and innovation development. The stages of smart city development in Denpasar City are influenced by 11 internal factors, 7 external factors, and 2 fundamental factors. In the case of Denpasar City, there is a new fundamental factor group in the form of local wisdom Tri Hita Karana and the Sewaka Dharma motto which are important factors in the development stage of a smart city.